Iron Mac : the legend of roughhouse cyclist Reggie McNamara - Homan, Andrew M., 1964- (University of Nebraska Press, 2016)
At a time when cycling in the United States rivaled baseball as the nation's most popular professional sport, along came Reggie McNamara, a farmer's son from Australia. Within a month of his arrival in the United States in 1913, he had earned the moniker Iron Man for his high tolerance of pain and his remarkable ability to recover from seemingly catastrophic injury. The nickname proved justified. But not only was he tough; he was also one of the best and highest paid athletes in the world. During his thirty-year career, McNamara won seventeen punishing six-day races along with an inestimable number of shorter distance races, including high-profile events on three different continents, peaking in 1926-27 at the age of thirty-nine. The fans, media, and his fellow professionals all idolized him as an example of the true grit needed to succeed in this grueling and dangerous sport. Late in his career, however, hard drinking and injuries took their toll, and McNamara became estranged from his wife and children. He fought back just as he always had on the race course, conquering his addiction to alcohol and becoming one of the earliest success stories of Alcoholics Anonymous. In this humorous and exciting biography of the original Iron Man, Andrew M. Homan pulls McNamara back into the spotlight, depictinga flawed but beloved man whose success in those unrelenting six-day races came at a price.